Optimization of Z-shaped assembled mortise and tenon joint box culvert connection and structural characteristics - Yuntao Yang; Hong Zhang; Longqi Liu; Baolei Zhu; Bingjie Song (PLoS ONE, 2025)
This paper proposes a new type of Z-shaped prefabricated mortise and tenon joint box culvert designed to enhance the longitudinal connection stability of highway prefabricated box culverts. Using actual engineering parameters and material properties, finite element simulation software was employed to analyze the culvert. The results indicated that maximum deformation and stress concentration occurred at the ends and armpits of the groove joint, specifically at the junction of the two culverts. The deformation of the middle section of the single culvert section is 75.86% higher than that of the end section. The deformation at the maximum deformation of the side wall of the single culvert section is 980% higher than that at the end. Under identical soil filling conditions, the mechanical properties of the integral box culvert and the prefabricated box culvert exhibited the greatest differences at their joint. The deformation and stress values at other locations showed minimal differences. Based on the stress and deformation characteristics of the culvert body, various box culvert designs with different joint heights and lengths were developed and simulated. The findings indicate that the mechanical properties of the joint culvert are most significantly enhanced with a joint height of 1.8 m and a joint length of 0.5 m. By integrating the advantages of the mortise and tenon joint structure—such as limiting joint displacement, preventing misalignment and uneven settlement, and facilitating smooth load transfer—the mortise and tenon joint is incorporated into the assembled box culvert joint. Ultimately, a Z-shaped prefabricated mortise and tenon joint box culvert, featuring a well-designed structure and a 1.25 m long mortise and tenon joint, was selected. Following optimization, the mechanical properties of the assembled box culvert joints have significantly improved. The connection performance is excellent, meeting the required bearing capacity, and demonstrating strong compressive shear and deformation resistance. Additionally, the yield and failure limits under identical uneven loads have been considerably enhanced, while maintaining economic and prefabrication rationality. This study provides valuable insights for the practical engineering of similar assembled box culverts.